2023
DOI: 10.3389/fpls.2023.1154088
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into metabolic and signalling events of directional root growth regulation and its implications for sustainable crop production systems

Abstract: Roots are sensors evolved to simultaneously respond to manifold signals, which allow the plant to survive. Root growth responses, including the modulation of directional root growth, were shown to be differently regulated when the root is exposed to a combination of exogenous stimuli compared to an individual stress trigger. Several studies pointed especially to the impact of the negative phototropic response of roots, which interferes with the adaptation of directional root growth upon additional gravitropic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 157 publications
0
7
0
Order By: Relevance
“…Different wavelengths of light spectrum can provide energy for photosynthesis, or act as a signal that informs plants about the quality of the light source (Miotto et al ., 2021; van Gelderen et al ., 2021). Plants express various photoreceptors that sense different wavelengths of light and accordingly trigger specific responses in the shoot, but also in the root (Van Gelderen, Kang and Pierik, 2018; Retzer and Weckwerth, 2021, 2023; Lopez et al ., 2023). While shoots are directly exposed to light, roots are usually shielded from direct illumination by the soil.…”
Section: The Negative Impact Of Direct Illumination On Root Growth An...mentioning
confidence: 99%
See 2 more Smart Citations
“…Different wavelengths of light spectrum can provide energy for photosynthesis, or act as a signal that informs plants about the quality of the light source (Miotto et al ., 2021; van Gelderen et al ., 2021). Plants express various photoreceptors that sense different wavelengths of light and accordingly trigger specific responses in the shoot, but also in the root (Van Gelderen, Kang and Pierik, 2018; Retzer and Weckwerth, 2021, 2023; Lopez et al ., 2023). While shoots are directly exposed to light, roots are usually shielded from direct illumination by the soil.…”
Section: The Negative Impact Of Direct Illumination On Root Growth An...mentioning
confidence: 99%
“…The root is a crucial organ that anchors the plant in the soil and facilitates water and nutrient uptake which is essential for plant growth and survival (Pierik and Testerink, 2014; Retzer and Weckwerth, 2021, 2023; Pree et al ., 2023). While it is relatively easy to measure and analyze the shoot phenotype of plants in the field or in the laboratory under physiological relevant conditions, it is still very difficult, time-consuming, or harmful for the root to obtain dynamic data of the whole root system (York, Griffiths and Maaz, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants evolved a fine-tuned network of intracellular processes to adapt to environmental changes leading to fast adaptation responses. Among other root growth responses, root hair outgrowth and exudate release belong to the so-called fast responses (Retzer and Weckwerth, 2021;Retzer and Weckwerth, 2023). Root hairs are extensions of the epidermal cells of roots that increase the surface area of the root and facilitate nutrient and water uptake from the soil (Grierson et al, 2014;Wu et al, 2019;Retzer and Weckwerth, 2021).…”
Section: Root Hairs Are Important For Plantmicrobe Interactionsmentioning
confidence: 99%
“…The increasing population and the loss of fertile soil requires holistic approaches to enhance sustainable agriculture (Retzer and Weckwerth, 2023). Studies have shown that cereal crops deficient in root hair outgrowth exhibit reduced fitness (Giehl and von Wireń, 2014;Lopez et al, 2023;Xu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%